Contested Authorities in the Haul of Sheikh Jumadil Kubro in Tralaya (State Islamic University (UIN) of Sunan Ampel Surabaya, 2021)
This study investigates the dynamics of the haul ceremony of Sheikh Jumadil Kubro in Tralaya, Mojokerto, East Java which is contested between KH Ismail’s family and the cultural figures supported by the local government. Using a qualitative research approach this study found that the haul ritual of Sheikh Jumadil kubro in Tralaya was held in two different versions, that is, Ismail's family carried out their haul ceremony called jam’ul jawami’, meanwhile Wulung as a figure of Sentonorejo Village initiated the haul ceremony of Sheikh Jumadil Kubro in the form of kirab budaya. This different ceremonial practice of haul leads to theological conflict. The house of Ismail accused Wulung and the administration of Sentonorejo Village of having made an innovation in religious practices (bid’ah) in the sense that kirab budaya was not taught by Sheikh Jumadil Kubro. Meanwhile, Wulung was convinced that the idea of kirab budaya incorporated within the haul ceremony of Sheikh Jumadil Kubro intended to preserve the Majapahit culture that is suitable with Sheikh Jumadil Kubro's religious teachings. However, although the contest between two actors of the haul ceremony was inevitable, they were able to meet and share in terms of economic interest.